2022
DOI: 10.3389/fphys.2022.834077
|View full text |Cite
|
Sign up to set email alerts
|

Rutin Inhibits Cardiac Apoptosis and Prevents Sepsis-Induced Cardiomyopathy

Abstract: Rutin is a flavanol-type polyphenol that consists of flavanol quercetin and the disaccharide rutinose, which has been reported to exert various biological effects such as antioxidant and anti-inflammatory activities. It is not clear whether rutin has a protective effect on sepsis-induced cardiomyopathy (SIC). In this study, we used male C57BL/6 mice and cecal ligation and puncture (CLP) surgery to establish the model of SIC. Rutin was precautionarily treated (50, 100, 200 mg/kg per day, 7 days) before CLP. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Genotoxicity, which has a damaging effect on DNA integrity, triggers apoptosis in macrophages [ 36 , 37 ]. In addition, TEGDMA induces DNA damage in gingival fibroblasts, lymphocytes, and oral keratinocytes [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genotoxicity, which has a damaging effect on DNA integrity, triggers apoptosis in macrophages [ 36 , 37 ]. In addition, TEGDMA induces DNA damage in gingival fibroblasts, lymphocytes, and oral keratinocytes [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous publication, rutin and quercetin, via suppressing oxidative stress and boosting antioxidant defense system, were labeled as chemopreventive agents against nephrocardiotoxicity induced by doxorubicin [8]. Most of other publications investigated the effects of rutin and quercetin on DXRinduced cardiotoxicity [29][30][31][32][33], but rare published studies assessed their effects on DXR-induced hepatotoxicity [34,35]. However, the mechanisms of actions were not entirely delineated by these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis-induced cardiac dysfunction is a common and severe complication of sepsis. 26 It has been studied extensively, but the specific pathogenesis is still not elucidated. In this study, we found that the expression of GP73 was increased in LPS-treated mouse hearts and LPS-cultured NRCMs.…”
Section: Discussionmentioning
confidence: 99%